Cruciform specimens used for determination of the influence of T-stress on fatigue crack growth with overloads on aluminum alloy Al 6061 T651 (Fracture and Structural Integrity, 2019)
The publication presents a cruciform specimen for the determination of cyclic crack growth data under biaxial loading. The design of the specimen with slotted loading arms allows good decoupling between the two loading directions. For different initial crack geometries, the solutions for the stress intensity factors KI and KII as well as the crack-parallel T-stress are calculated by linear elastic finite element analysis (FEA) with the program ABAQUS. For two specimens with the same geometry made of aluminum alloy 6061 T651, the crack growth behaviour is measured at different T-stresses at a stress ratio of R=0.7 and overloads. It is shown that the crack retardation after an overload with crack-parallel tensile stress is less than without it. The reason for this behaviour is considered to be the reduced plasticity at the crack tip due to the higher triaxiality of the stress state.
Keywords: Fracture mechanics; cruciform specimen; fatigue crack growth; stress intensity factor; biaxial testing; overload